2019
DOI: 10.14254/2071-8330.2019/12-2/4
|View full text |Cite
|
Sign up to set email alerts
|

R&D accounting treatment, firm performance, and market value: Biotech firms case study

Abstract: This study examines the correlation between R&D accounting treatment and market value in association with the firm's performance, with a focus on biotech firms. Firstly, the results of the analysis show that capitalized R&D has a positive correlation with market value, consistent with existing literature. In the case of biotech firms, capitalized R&D has a higher value relevance compared to other industries. Secondly, this study examines the effect of a decrease in capitalized R&D on market value. It is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Studies by Isiker and Tas (2021), Wang et al (2021), Feito-Ruiz et al (2020, Marangu et al (2019), Heavilin and Songur (2019), Chang et al (2019), Lee (2019), Arulsulochana (2019), Khanal and Mishra (2017), Dedman et al (2017), De Ridder andBurnie (2016) and many others have also concluded a positive impact of BSA.…”
Section: Discussionmentioning
confidence: 92%
“…Studies by Isiker and Tas (2021), Wang et al (2021), Feito-Ruiz et al (2020, Marangu et al (2019), Heavilin and Songur (2019), Chang et al (2019), Lee (2019), Arulsulochana (2019), Khanal and Mishra (2017), Dedman et al (2017), De Ridder andBurnie (2016) and many others have also concluded a positive impact of BSA.…”
Section: Discussionmentioning
confidence: 92%
“…In case of Korean biotech firms, capitalized R&D has a higher value relevance compared to other industries. A large amount of R&D invested in the biotech industry and its capitalization are considered as key to the future sustainable success of these firms [ 46 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following previous studies (e.g. Buchanan et al, 2018;Khaoula & Moez, 2019;Lee, 2019;Ni et al, 2019) the firm value is proxied by Tobin's Q. Earnings which is revenues minus expenses is measured by net income divided by total assets (Wang, 2019).…”
Section: Literature Review and Hypotheses − The Impact Of Large Deferred Tax And Accruals On The Relationship Between Earnings And Firm Vmentioning
confidence: 99%